Diagnosis and Treatment of Psychiatric Comorbidity in a Patient with Charles Bonnet Syndrome - Chen, Jasper J. (Case Reports in Psychiatry, 2014)
Background. A significant proportion of patients with neurological disorders may have comorbid psychiatric symptomology, which may be managed by primary outpatient neurologists. Referral to their psychiatric colleagues is mediated by available consultation-liaison units and according to clinical opinion. Aims of Case Report. We present the case of a patient whose initial referral to epilepsy clinic led to a workup which ultimately diagnosed her with nonepileptic seizures (NES). In the course of her follow-up, she developed intractable headaches, and worsening mood symptoms and eventually exhibited Psychotic Features for which psychiatry became coinvolved in her care. Major Depression with Psychotic Features and Charles Bonnet syndrome were considered as a likely comorbid diagnoses. Her pharmacologic management on venlafaxine and quetiapine eventually caused substantial amelioration of her psychiatric symptomology as longitudinally followed by PHQ-9 and GAD-7 scores. Conclusion. Optimal evaluation and management of mental illness in patients with complex neurologic symptomology may require independent evaluation and treatment by psychiatrists when clinically appropriate.